Diversidade multiusuário em sistemas cooperativos com múltiplos relays: um esquema de seleção eficiente e de baixa complexidade - Melo, Marco Antonio Beserra de (2012)
On this work, it is proposed an efficient low-complexity selection scheme for multiuser multi-relay downlink cooperative networks comprised of one source node, L destination nodes, and N relay nodes. The proposed scheme first selects the best destination node based on the channel quality of the direct links and then selects the best relay that yields the best path from the source to the selected destination. Assuming both decode-and-forward and amplify-and-forward relaying strategies, the performance of the considered system is investigated. Closed-form expressions for the outage probability are obtained and validated by means of Monte Carlo simulations. Comparisons with the optimal selection scheme are performed and shows that the performance of the proposed scheme is very close to that of the optimal selection scheme, with the proposed scheme having the advantage of lower complexity than the optimal scheme. Furthermore, in our analysis, the source node may be equipped with either a single antenna or M multiple antennas. An asymptotic analysis is carried out, and it reveals that, regardless of the relaying strategy employed, the diversity order reduces to L+N for the single-antenna source case, whereas it is equal to ML+N for the multiple-antenna source case. The effects of the number of relay and destination nodes on the system performance and its influence on the best relay position are examined. In addition, a trade-off concerning the system performance and spectral efficiency is observed when multiple antennas are employed at the source node.